EFFICACY OF SIMPLE BLEACH DIGESTION OF SPUTUM IN THE DIAGNOSIS OF PULMONARY TUBERCULOSIS BY MICROSCOPIC EXAMINATION - Yin Leong, Grace Corrine Khong; Sharon, Leesha; Pandey, Pooja; Guldar, Nadeem; BHAT K, GOPALKRISHNA (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Rapid diagnosis of pulmonary tuberculosis (PTB) depends on microscopic examination of sputum smear for acid-fast bacilli (AFB). The direct microscopy examination lacks sensitivity. It needs at least 10,000 AFB/ml of sputum to observe in the smear. The objective of this study was to determine the efficacy of three different short-term bleach digestions and concentration of sputum in the diagnosis of PTB. Methods: A total of 171 sputum samples collected from patients suspected of having pulmonary TB were used. Direct smear was prepared using each sample and then divided into three parts to which equal volume of 5% bleach was added. The first part was kept at room temperature for 45 minutes with intermittent shaking. The second part was allowed to stand at room temperature for 45 minutes for sedimentation, and the third part was kept at room temperature for 45 minutes and then centrifuged at 3000 g for 15 minutes for deposit formation. Smears were prepared and stained with Ziehl-Neelsen method and observed for AFB using Revised National TB Control Programme Guidelines. Results: Out of 171 sputum samples, 45 (26.32%), 48 (28.07%), 49 (28.65%), and 55 (32.16%) of specimens were positive by direct, bleach digested mixed method, bleach digested sedimented method, and centrifugation method, respectively. The background of the bleach digested sputum smears was clear. Conclusion: Short-term bleach digestion of sputum improves the sensitivity of microscopic examination and the number of AFB observed in the smear. Bleach being a disinfectant kills AFB and makes handling of sputum safer.